Advancing the diagnostic value of the Pro-agility Test - Forster, J. W.; Uthoff, A. M.; Rumpf, M. C.; Cronin, J. B. (Journal of Athletic Enhancement, 2021)
The pro-agility shuttle is commonly used by practitioners to assess Change of Direction (COD) performance in athletes. The metric of total time is influenced by accelerative and declarative ability and makes "true" COD ability difficult to quantify. The aim of this study was to determine whether an advanced diagnostic protocol, with three timing lights, could be used to reliably measure different components of pro-agility shuttle performance. The traditional set-up was adapted, and additional timing lights were placed 2.28 m from each COD line, enabling different phases of COD performance to be quantified. Ten participants (age: 16.1 ± 0.32 y, height: 1.81 ± 0.11 m, body mass: 76.6 ± 18.04 kg) completed three sessions, consisting of three trials, separated by one week. Absolute and relative consistency was assessed using Coefficients of Variation (CV) and Infraclass Correlation Coefficients (ICC) respectively. A one-way ANOVA was performed to determine whether between-day performance differences existed. Systematic changes were identified between sessions 1-2 for COD1, Moderate Intensity 501, Moderate intensity 105, Stationary 5-0-5 and Flying 5-0-5 (-7.37%, -4.20%, p0.90) for all sub-tests. It would seem that the components of the pro-agility test can be measured reliably and therefore can provide valuable diagnostic information to the practitioner to guide COD programming.